Mapas táteis como recursos didáticos-suporte para o ensino de ciências aos alunos com deficiência visual - Heinzen, Valdite Aparecida (2015)
Our goal was to investigate both the production and the use or not of tactile maps as learning-support resources for teaching science to students with visual impairment, as well as identify needs to indicate the proposition of continuing education in producing tactile maps for teachers serving students with visual impairment. The research’s problem was how tactile maps can serve as a significant learning-support resources for mediation of teaching and learning science content to visually impaired elementary school students? The hypothesis is that the tactile maps (sensory elements) allow the tactile perception and mentalizing concepts through representative objects, enabling the student to meaningful understanding and expanding their learning opportunities. We use the bibliographical research, documentary and survey, using the questionnaire as a dice technique collection applied to 27 teachers who work in the Resource Rooms Multifunction of state schools of Cuiabá and Várzea Grande. For dice analysis we use basic statistical techniques (with representation in graphs and tables) and document analysis. The results indicate that 22 teachers are effective, 9 contracted predominantly pedagogues with expertise in educational specialized services who have between 36-45 years of age. Some topics studied in the Multifunction Resource living rooms are related to the science content in Elementary Education. We notice that the lack of resources as Assistive Technology, therefore the nominees are not actually ("computer", "internet" and "TV"). The 31 teachers say that they use concrete materials, but most of them do not produce educational materials to serve as a didactic support for teaching science for visually impaired students. As for continuing education we noted that none of the formations informed refer to the production of teaching materials and, in particular, production of tactile maps or materials embossed for teaching science for students with visual impairment. Among the difficulties faced are the lack of teaching materials and adapting/making materials for specialized educational services. As a possible solution for the difficulties, the teachers pointed the continuing education and the existence of adapted materials. From the survey we see the need to present to teachers who work with visually impaired students grants to assist their teaching practice, promoting adapted courseware production possibilities (tactile maps) that comply with the educational specificity of these students.